Development of the Augmented Reality Book on the Material of the Sense of Smell and Taste to Improve Learning Outcomes - Wardah, Triana Novita; Andriani, Aldina Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Teachers have not been optimal in preparing teaching materials for technology-based sense of smell and taste materials, causing low cognitive learning outcomes for students. This study aims to describe the development design, test the feasibility and effectiveness of the Augmented Reality Book to improve the learning outcomes of IVA class students of SDN Kalibanteng Kidul 03, Semarang City. The type of research is Research and Development (R&D) with the Borg and Gall model. The research subjects were IVA class students of SDN Kalibanteng Kidul 03, Semarang City, totalling 21 students. Data collection techniques used tests (pre-test and post-test) and non-tests (observation interviews, questionnaires, and documentation). Data analysis techniques used normality test, t-test, and N-Gain test. The results showed that the Augmented Reality Book development design used Assemblr EDU, Canva and Heyzine applications with main page components, instructions for use, activity instructions, intended competencies, Project-Based Learning syntax-based materials, AR barcodes containing visual media in the form of 3D images using Assemblr EDU, LKPD, and evaluation using Wordwall. The feasibility of Augmented Reality Book from material experts is 91.25% and media experts are 92.18% which are very feasible criteria, supported by the results of the analysis of teacher response questionnaires of 95% and student response questionnaires of 99.3% which are also very feasible criteria. The effectiveness of the Augmented Reality Book is shown by an increase in pre-test and post-test of 28.4, supported by the results of the t-test, 0.001, and the N-Gain score of 0.6595, medium criteria. The conclusion of this study shows that Augmented Reality Book material successfully develops the sense of smell and taste, is very feasible, and effective in improving the science learning outcomes of IVA class students SDN Kalibanteng Kidul 03 Semarang City on the material sense of smell and taste.